Seed germination of Quercus robur, q. pyrenaica and q. ilex and the effects of smoke, heat, ash and charcoal - Reyes, Otilia; Casal, Mercedes (Ann. For. Sci., 2006)
This study is centred on Quercus robur, Q. pyrenaica and Q. ilex that have a distribution area covering all Europe. Fire is a frequent ecological factor in many ecosystems, especially in those with Mediterranean climates. Our working hypothesis is that fire affects the germination process. An experiment was carried out testing the following treatments: Control, Smoke-5 min, Smoke-10min, Smoke-15 min, 60 ºC-5 min, 60 °C-15 min, 90 ºC-5 min, 110 ºC-5 min, 150 ºC-5 min, Ash, Ash Dilution and Charcoal. The seed incubation was spread over a year. The germination rates of the Control are very high, especially in Q. ilex. Almost none of the treatments inhibit germination and only the Q. ilex seeds, when subjected to 150 ºC-5 min, show a marked inhibition. Q. robur and Q. pyrenaica take a year to complete their germination, while Q. ilex only takes 22 weeks. Probably, this reproductive behaviour is related to the climate characteristics to which the species have become adapted. Finally, fire does not determine the germination process, the recruitment of new individuals being independent of fire.
Keywords: fire; germination; Quercus; reproductive strategies; Seeds